Bojarite, Cu3(N3C2H2)3(OH)Cl2⋅6H2O, a new mineral species with a microporous metal–organic framework from the guano deposit at Pabellón de Pica, Iquique Province, Chile. (30th December 2020) - Chukanov, Nikita V.; Möhn, Gerhard; Zubkova, Natalia V.; Ksenofontov, Dmitry A.; Pekov, Igor V.; Agakhanov, Atali A.; Britvin, Sergey N.; Desor, Joy
Abstract: The new triazolate mineral bojarite (IMA2020-037), Cu3 (N3 C2 H2 )3 (OH)Cl2 ⋅6H2 O, is found in a guano deposit located at the Pabellón de Pica Mountain, Iquique Province, Tarapacá Region, Chile. Associated minerals are salammoniac, halite, nitratine and belloite. Bojarite occurs as blue fine-grained porous aggregates up to 1 mm × 3 mm × 5 mm combined typically in interrupted earthy crusts. The mineral is brittle. The Mohs hardness is 2. D calc = 2.057 g cm –3 . The IR and Raman spectra show the presence of the 1, 2, 4-triazolate anion and H2 O molecules. Bojarite is optically isotropic and n = 1.635(2) (λ = 589 nm). The chemical composition (electron-microprobe data for Na, Mg, Fe, Cu and Cl; H, C and N contents measured by gas chromatography on products of ignition at 1200°C; wt.%) is: Na 0.22, Mg 0.74, Fe 0.99, Cu 29.73, Cl 13.62, N 20.4, C 11.6, H 3.3, O (calculated by stoichiometry) 19.93, total 100.53. The empirical formula is (Cu2.68 Mg0.17 Fe0.10 Na0.05 )Σ3 (N3 C2 H2 )2.755 [(OH)][Cl2.19 (H2 O)3.77 (OH)0.04 ]Σ6 ⋅2.3H2 O. The idealised formula is Cu3 (N3 C2 H2 )3 (OH)Cl2 ⋅6H2 O. The crystal structure of bojarite was refined based on powder X-ray diffraction data, using the Rietveld method. The final agreement factors are: R p = 0.0225, Rw p = 0.0310 and R obs = 0.0417. The new mineral is cubic, space group Fd $\bar{3}$ c ; a = 24.8047(5) Å, V = 15, 261.6(5) Å 3 and Z = 32. The strongest reflections of the powder X-ray diffraction pattern [ d, Å ( I, %)( hkl )] are: 8.83 (31)(220), 7.19 (100)(222), 6.23 (35)(400), 5.077 (28)(422), 4.194 (28)(531), 3.584 (23)(444), 2.865 (28)(660, 751) and 2.723 (22)(753, 842).